Endobronchial ultrasound-guided transbronchial mediastinal cryobiopsy in the diagnosis of mediastinal lesions: safety, feasibility and diagnostic yield – experience in 50 cases - Ariza-Prota, Miguel; Pérez-Pallarés, Javier; Fernández-Fernández, Alejandro; García-Alfonso, Lucía; Cascón, Juan A.; Torres-Rivas, Héctor; Fernández-Fernández, Luis; Sánchez, Inmaculada; Gil, Maria; García-Clemente, Marta; López-González, Francisco (ERJ open research, 2023)
Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the technique of choice in the study of mediastinal and hilar lesions; however, it can be affected by the insufficiency of intact biopsy samples, which might decrease its diagnostic yield for certain conditions, thus requiring re-biopsies or additional diagnostic procedures such as mediastinoscopy when the probability of malignancy remains high. Our objectives were to 1) attempt to reproduce this technique in the same conditions that we performed EBUS-TBNA, in the bronchoscopy suite and under moderate sedation; 2) describe the method used for its execution; 3) determine its feasibility by accessing different lymph node stations applying our method; and 4) analyse the diagnostic yield and its complications. This was a prospective study of 50 patients who underwent EBUS-TBNA and EBUS-guided transbronchial mediastinal cryobiopsy (TMC) in a single procedure using a 22-G TBNA needle and a 1.1-mm cryoprobe subsequently between January and August 2022. Patients with mediastinal lesions >1 cm were recruited, and EBUS-TBNA and TMC were performed in the same lymph node station. The diagnostic yield was 82% and 96% for TBNA and TMC, respectively. Diagnostic yields were similar for sarcoidosis, while cryobiopsy was more sensitive than TBNA in lymphomas and metastatic lymph nodes. As for complications, there was no pneumothorax and in no case was there significant bleeding. There were no complications during the procedure or in the follow-up of these patients. TMC following our method is a minimally invasive, rapid and safe technique that can be performed in a bronchoscopy suite under moderate sedation, with a higher diagnostic yield than EBUS-TBNA, especially in cases of lymphoproliferative disorders and metastatic lymph nodes or when more biopsy sample is needed for molecular determinations.